Default of the Construction Service Provider as a Reason for Termination of the Construction Work Contract - Pratama, Febrian Rizki; Abdillah, Maulana Farhan; Nuralify, Mohammad; Damayanti, Astri; AR, Febriyanti Putri (Faculty of Law, Universitas Pekalongan, 2024)
Termination of a construction contract can be carried out if it arises as a result of failure to fulfill the obligations of one of the parties, in this case a wanprestatie occurs. Therefore, what form of wanprestatie is committed by the service provider is the reason for terminating the contract and what legal remedies can be taken to terminate the construction contract due to wanprestatie. The aim of this research is to analyze the form of wanprestatie by service provider as a reason for terminating the contract and analyzing the legal remedies taken by the construction service provider to terminate the contract due to wanprestatie. This research uses normative legal research using statute approaches, conceptual approaches, and case approaches. The first result is that the form of contract termination is in the form of a fundamental error with a benchmark, namely a form of wanprestatie committed by the service provider as a reason for terminating the contract by the service user, namely in the form of a fundamental error, such as work delays with a benchmark, namely the service provider has not been able to fulfill the work progress specified. It is agreed by the service user or service provider that they have not carried out their work after one month of signing the contract so that the service user gives a warning letter to the service provider to be given time to correct their negligence within the specified time period, which is done by giving a warning letter 3 (three) times. The second result is that service providers can take legal remedies against unilateral contract termination if they go through non-litigation, then they can take deliberation, mediation, conciliation and arbitration. Not only that, settlement can also be done through a dispute council. If using litigation, the service provider can make file a lawsuit in the District Court.